Role of social and other determinants of health in the effect of a multicomponent integrated care strategy on type 2 diabetes mellitus - Rubén Silva-Tinoco; Teresa Cuatecontzi-Xochitiotzi; Viridiana De la Torre-Saldaña; Enrique León-García; Javier Serna-Alvarado; Eileen Guzmán-Olvera; Dolores Cabrera; Juan G. Gay; Diddier Prada (International Journal for Equity in Health, 2020)
Abstract Background Although important advances in treatment strategies have been developed in type 2 diabetes mellitus (T2DM), large gaps exist in achieving glycemic control and preventing complications, particularly in low-and middle-income countries, which suggests a potential effect of social determinants of health (SDH, i.e., education level and socioeconomic status). However, few studies have determined the role of SDH and other determinants of health (ODH, i.e., diabetes knowledge and self-care scores) in achieving T2DM goals during effective multidisciplinary interventions. We aimed to examine a multicomponent integrated care (MIC) program on diabetes care goals and determine the effect of SDH and ODH on T2DM patients. Methods A before-and-after design (a pretest, a 5-month intervention, and a follow-up) was used in a T2DM population from Mexico City. The SDH included education level and socioeconomic status; the ODH included diabetes knowledge, self-care scores, and deltas (i.e., differences between baseline and follow-up scores). The triple-target goal (glycated hemoglobin, blood pressure, and LDL-cholesterol) was established as a measurement of T2DM goals. Results The DIABEMPIC (DIABetes EMPowerment and Improvement of Care) intervention (n = 498) reduced the glycated hemoglobin levels (mean reduction 2.65%, standard deviation [SD]: 2.02%) and cardiometabolic parameters; it also improved health-related quality of life. From 1.81% at baseline, 25.9% of participants (p-value< 0.001) achieved the triple-target goal. We found a significant association between education level (p-value = 0.010), diabetes knowledge at baseline (p-value = 0.004), and self-care scores at baseline (p-value = 0.033) in the delta (change between baseline and follow-up assessments) of HbA1c levels. Improvements (increase) in diabetes knowledge (p-value = 0.006) and self-care scores (p-value = 0.002) were also associated with greater reductions in HbA1c. Conclusions MIC strategies in urban primary care settings contribute to control of T2DM. SDH, such as education level, and ODH (diabetes knowledge and self-care scores at baseline) play a key role in improving glycemic control in these settings.